Pengaruh Good Corporate Governance, Ukuran Perusahaan Dan Leverage Terhadap Kinerja Keuangan Perusahaan - shafirah, Mirathus; Suwandi, Suwandi (Jurnal Akuntansi dan Keuangan, 2024)
The point of this examination is to look at how the impact of GCG rehearses is addressed by the leading group of magistrates, free chiefs, review board of trustees and institutional possession, organization size is estimated by Ln all out deals and influence is estimated by monetary execution obligation to-value proportion (DER) is estimated by return on value (ROA). The number of inhabitants in this examination is organizations from different modern areas and the customer merchandise industry that have been recorded on the Indonesia Stock Trade for the 2019-2022 period. This exploration utilizes quantitative strategies with an example that meets the purposive examining strategy of 75 organizations (300 perception information), utilizing different straight relapse investigation techniques. By taking into account the aftereffects of examination investigation and conversation discoveries, it is reasoned that GCG, organization size and influence significantly affect the organization's monetary exhibition